2020
DOI: 10.1523/jneurosci.2667-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Impairment of Olfactory Behavior and Signaling Mediated by an Olfactory Corticofugal System

Abstract: Processing of olfactory information is modulated by centrifugal projections from cortical areas, yet their behavioral relevance and underlying neural mechanisms remain unclear in most cases. The anterior olfactory nucleus (AON) is part of the olfactory cortex, and its extensive connections to multiple upstream and downstream brain centers place it in a prime position to modulate early sensory information in the olfactory system. Here, we show that optogenetic activation of AON neurons in awake male and female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…The abundant top-down influence from olfactory cortices to the MOB mainly targets the granule cells (for a review of the MOS, see Brann and Datta 2020;Schäfer et al this issue). Top-down influence on MOB by the AON and the anterior piriform cortex has been described previously (Boyd et al 2012(Boyd et al , 2015Markopoulos et al 2012;Rothermel and Wachowiak 2014;Oettl et al 2016;Quintela et al 2020 and reviewed by Rothermel et al this issue).…”
Section: Autism Candidate Genes In Olfactory Circuit Wiringmentioning
confidence: 73%
“…The abundant top-down influence from olfactory cortices to the MOB mainly targets the granule cells (for a review of the MOS, see Brann and Datta 2020;Schäfer et al this issue). Top-down influence on MOB by the AON and the anterior piriform cortex has been described previously (Boyd et al 2012(Boyd et al , 2015Markopoulos et al 2012;Rothermel and Wachowiak 2014;Oettl et al 2016;Quintela et al 2020 and reviewed by Rothermel et al this issue).…”
Section: Autism Candidate Genes In Olfactory Circuit Wiringmentioning
confidence: 73%
“…AONpP sends, similar to PC, sensory-evoked feedback to the OB (Rothermel and Wachowiak 2014 ) but only a few studies have investigated the influence of centrifugal AONpP projections on in vivo OB circuit function. Activation of AONpP derived fibers strongly inhibits sensory signaling of olfactory output neurons both in the anesthetized (Markopoulos et al 2012 ; Medinaceli Quintela et al 2020 ) as well as in the awake behaving mouse (Medinaceli Quintela et al 2020 ) suggesting a type of gating function. In contrast to that, AONpE corticofugal projections seem to be exclusively contralateral (Schoenfeld and Macrides 1984 ; Yan et al 2008 ).…”
Section: Cortical Top-down Modulationmentioning
confidence: 99%
“…These existing granule cells in their turn inhibit mitral cells, thought to increase the discriminatory potential of the OB network. The paradigm of our continuous stimulation might have caused a long-term inhibition of the OB network, blocked all sensory input, and therefore mimicked sensory deprivation as occurred through optogenetic activation of the AON in a very recent study (Medinaceli Quintela et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…This leaves us to the discussion, why AON activation would lead to a decrease in newborn neurons. Multiple studies have demonstrated that the AON can regulate the inhibitory network in the OB by activation of granule cells (Markopoulos et al, 2012;Medinaceli Quintela et al, 2020;Oettl et al, 2016). These existing granule cells in their turn inhibit mitral cells, thought to increase the discriminatory potential of the OB network.…”
Section: Discussionmentioning
confidence: 99%